SYMBOLIC MEANING OF THE MAKASSAR TRIBE HOMES IN GOWA REGENCY, SOUTH SULAWESI (SEMIOTICS APPROACH) - Herlisa Herlisa; Lukman Lukman; Gusnawaty Gusnawaty (Universitas Muhammadiyah Tapanuli Selatan, 2021)
This study aims to describe the symbolic meaning of the traditional house of the Makassar tribe. This descriptive analysis research used an inductive approach that describes facts, circumstances, variables and phenomena that occured during research. The data was collected and analyzed using the semiotics study. The results of the study show that in general the direction of the Makassar Tribal residential buildings were facing all directions or it could also be facing one direction only. This relates to the cosmological view of the Makassar Tribe, namely 'Appa', which considers the world to be quadrangular, meaning that all contents are equal. The striking difference in Makassar tribal residences can be distinguished based on their social stratification divided into three groups namely: Karaeng group (nobility), Tu Maradeka group (independent people), and Ata group (slave servants). The most striking differences in physical form between aristocrats and ordinary people in the Makassar Tribal house can be seen from the timba 'sila/sambulayang, tuka', and anjong. The construction of Makassar houses adheres to the customs they believe in because they have profound meanings to their lives.